ANALISIS EFISIENSI EKONOMI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI PADI SAWAH DI KECAMATAN JANGKAT KABUPATEN MERANGIN PROVINSI JAMBI - Oktavia, Rini; Kernalis, Emy; Oktari Ulma, Riri (Universitas Jambi, 2019)
This research was conducted with the aim to analyze the economic efficiency of the use of production factors on rice farming in District of Jangkat Regency Merangin Jambi Province. Site selection was done deliberately with the consideration that the District of Jangkat is the district with the second largest rice field production in Merangin District so it is also one of the rice farming centers in Merangin District. Sampling method using the methods of simple random sampling with a respondent as much as 57 number of farmers. Data analysis using the method of multiple linear regression analysis and efficiency analysis with SPSS application. Production factors such as land area, labor, seed, fertilizers also eradication of pests and plant diseases used by farmers are suspected not yet economically efficient. The results showed that there are 4 factors with the error rate (5%) contributing significantly to the rice production, the spesific factor is land area, seeds, fertilizers and eradication of pests and plant diseases . This proves that the factor of labor does not significantly affect to the rice production. Meanwhile the value of Economic Efficiency of paddy rice farming is 0,85 which means the use of production factor of paddy field farming in District of Jangkat not efficient economically.